Misery And Faithfulness In “Aku Ini Binatang Jalang” Anthology Of Poetry By Chairil Anwar: Paul Ricoeur’s Hermeneutics Review - Novira Aprianti Suci; Nensilianti Nensilianti; Faisal Faisal (Phonologie : Journal of Language and Literature, 2021)
Abstract. This study aims to describe the interpretation of the symbols of misery and the symbols of loyalty contained in the poetry anthology Aku Ini Binatang Jalang by Chairil Anwar using the Hermeneutic theory of Paul Ricoeur. This study used qualitative research methods. The data in this study are poetry quotes in the form of sentences that describe symbols of misery and symbols of loyalty experienced by Chairil as a writer in nine poems. The data source in this research is the poetry anthology Aku Ini Binatang Jalang by Chairil Anwar. The data collection techniques in this study were reading techniques and note taking techniques. The analysis of this research was carried out by identifying, classifying, analyzing, and describing symbols of misery and symbols of loyalty in the poetry anthology Aku Ini Binatang Jalang by Chairil Anwar with a review of Paul Ricouer's Hermeneutics.